Blended E-Learning in Islamic Religious Education: A Qualitative Case Study of Student Engagement and Instructional Interaction in An Indonesian Madrasah - Handaru Kusbiantoro; Joko Subando (LaKaspia, 2026)
This study explores the implementation and perceived contribution of blended e-learning to student engagement and instructional interaction in Islamic Religious Education at MA Al-Azzaam Semarang, Indonesia. The study employed a qualitative case study design. Data were collected through non-participant classroom observations, semi-structured interviews, and document analysis involving eight purposively selected participants, consisting of one madrasah leader, two Islamic Religious Education teachers, and five students. The data were analyzed through data condensation, data display, and conclusion drawing, while source and method triangulation were used to enhance the credibility of the findings. The results indicate that e-learning was implemented through a blended learning model combining face-to-face instruction with Google Classroom, Google Meet, and WhatsApp. Participants perceived that this model facilitated access to learning materials, supported student participation and independent learning, and expanded communication between teachers and students beyond classroom hours. However, its implementation was constrained by unstable internet connectivity, differences in students’ digital literacy, and limited opportunities for direct moral guidance and teacher role modelling. Face-to-face instruction therefore remained essential for religious practice, character development, and the internalization of Islamic values. The study suggests that the contribution of e-learning to Islamic Religious Education depends not merely on the availability of digital technology, but on the pedagogical allocation of online and face-to-face activities according to their respective instructional functions. These findings provide practical implications for madrasahs seeking to develop context-sensitive and value-oriented blended learning.